Historical and Multidisciplinary Perspectives on Hope 2020
DOI: 10.1007/978-3-030-46489-9_11
|View full text |Cite
|
Sign up to set email alerts
|

Hope in Health Care: A Synthesis of Review Studies

Abstract: The objectives of this study were (1) to provide an overview of review studies on hope in health care, and to describe (2) conceptualizations of hope, (3) antecedents and consequences of hope, and (4) ethical topics related to hope. Electronic databases were searched and 73 review studies were selected and thematically analyzed. Hope was conceptualized as (a) an expectation: appraisal of a future outcome, (b) resilience: endurance of adversity, and (c) a desire: expression of meaning. Opposite concepts to hope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 88 publications
0
18
0
2
Order By: Relevance
“…Furthermore, motivation and belief in their own abilities are two internal states required to cope with the difficulties caused by PD symptoms ( 5 ) that may have supported the coping mechanisms of participants in MdlV who reported feeling motivated at the end of the sessions and believing more in themselves, in the possibility of improvement, or in their ability to communicate despite imperfect speech. This mechanism can be related to the experience of hope, a sentiment that plays a key role in the process of care and resilience in chronic illness ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, motivation and belief in their own abilities are two internal states required to cope with the difficulties caused by PD symptoms ( 5 ) that may have supported the coping mechanisms of participants in MdlV who reported feeling motivated at the end of the sessions and believing more in themselves, in the possibility of improvement, or in their ability to communicate despite imperfect speech. This mechanism can be related to the experience of hope, a sentiment that plays a key role in the process of care and resilience in chronic illness ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…This relational co-construction of hope “can increase the potential for uncertainty and abstraction even further, all the while maintaining the positive meaning-making allure of being hopeful” [ 6 ] (p. 1). Recently, a synthesis of review studies stressed that “hope was conceptualized as an expectation (appraisal of a future outcome), resilience (endurance of adversity), and a desire (expression of meaning)” [ 8 ] (p. 197).…”
Section: Introductionmentioning
confidence: 99%
“…Hope is also to be conceptualized as an intrinsic force associated with better emotional and stress coping ( Lu and Cui, 2016 ). It not only plays an indispensable role in developing positive anticipatory goals but is also an essential resource to help individuals cope with physical and mental pain ( Olsman, 2020 ). Berendes et al (2010) found that hope can reduce stress and depression in individuals; Alacorn et al (2013) combined results from 26 studies involving 4,023 participants and found a significant negative association between hope and depression.…”
Section: Introductionmentioning
confidence: 99%